100 social innovations from Finland - Taipale, Ilkka; Sur, Zona; McCracken, Don; Malkki, Eva; Taipale, Pilvi Riitta; McCracken, Don (Kirjokansi, 2013)
"One might wonder what a single-chamber parliament, dish drying cabinets and text messaging have in common. Or what the link is between maternity packs, xylitol, the sauna and free school meals. The answer is simple: they are all Finnish social innovations. In Finland, as elsewhere, technical inventions have hogged all the economic limelight, but it is only recently that social innovations have been highlighted as the foundation of societal harmony. Gender equality, free education, universal social security and parliamentary democracy, and the consequent social stability they create, have secured Finland's welfare. This book, which is both serious and entertaining, presents 100 Finnish social innovations." -- (Back Cover)
Keywords: Social Values; Cultural Characteristics; Social Welfare; Community Health Services; kansalaisyhteiskunta; kulttuuri; suomalaiset; sosiaaliset innovaatiot; yhteiskuntapolitiikka; hyvinvointivaltio; julkinen hallinto; sosiaalipolitiikka; terveyspolitiikka; kulttuuripolitiikka; kansainvälistyminen; sosiaalitekniikka; arki; keksinnöt; elämäntapa; suomalaisuus; sociala innovationer; samhällspolitik; välfärdsstat; offentlig förvaltning; socialpolitik; hälsopolitik; kulturpolitik; internationalisering; medborgarsamhälle; social teknik; vardag; uppfinningar; livsstil; finskhet; yhteiskunnalliset arvot; kulttuurin ominaispiirteet; sosiaalihuolto; julkiset terveyspalvelut; Suomi